Окремі патогенетичні механізми функціональних кіст яєчників та їхніх ускладнень = Functional ovarian cysts and their complications certain pathogenetic mechanisms - Nazarenko, O. Ya.; Vastyanov, R. S. (Journal of Education, Health and Sport, 2015)
Nazarenko O. Ya., Vastyanov R. S. Окремі патогенетичні механізми функціональних кіст яєчників та їхніх ускладнень = Functional ovarian cysts and their complications certain pathogenetic mechanisms. Journal of Education, Health and Sport. 2015;5(9):599-612. ISSN 2391-8306. DOI10.5281/zenodo.31725 http://dx.doi.org/10.5281/zenodo.31725 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A599-612 https://pbn.nauka.gov.pl/works/640864 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015. УДК 618.14-002-08:615.849 ОКРЕМІ ПАТОГЕНЕТИЧНІ МЕХАНІЗМИ ФУНКЦІОНАЛЬНИХ КІСТ ЯЄЧНИКІВ ТА ЇХНІХ УСКЛАДНЕНЬ FUNCTIONAL OVARIAN CYSTS AND THEIR COMPLICATIONS CERTAIN PATHOGENETIC MECHANISMS О. Я. Назаренко, * Р. С. Вастьянов O. Ya. Nazarenko, * R. S. Vastyanov Військово-медичний клінічний центр Південного регіону, Одеса; *Одеський національний медичний університет, Одеса. Military-Medical Clinical Centre of the South Region, Odessa; *Odessa National Medical University, Odessa Summary A review of the modern scientific literature is dedicated to the functional ovarian cysts and their complications (in the form of ovarian apoplexy) pathogenetic mechanisms. Functional cysts (follicular, corpus luteum and theca-lutein-induced) etiopathogenesis is rather complicated due to many causes and pathogenic mechanisms. The sequences caused by their complicated clinical manifestation can be lead to immediate surgical intervention and female reproductive system functional activity failure. The recurrent manifestation is the functional ovarian cysts peculiarity together with their related complications such as ovarian apoplexy. The investigation of functional ovarian cysts pathogenetic mechanisms will not only improve the results of anovulatory infertility treatment but will offer pathogenetically reasonable prevention of this acute surgical pathology. Functional ovarian cysts and their complications reduced recurrence lead to number of operated patients decrease that has a positive effect on the female reproductive and menstrual function. Ключові слова: ovarian apoplexy, functional cysts, pathogenetic mechanisms. Резюме Наведений огляд сучасної літератури з питання патогенезу функціональних кіст яєчників і характерного для них ускладнення - апоплексії яєчника. Етіопатогенез функціональних (фолікулярних, жовтого тіла і тека-лютеїнових) кіст достатньо складний через безліч причин і патогенетичних механізмів. У випадках, що не супроводжуються якимось клінічними проявами, утворення функціональних кіст яєчників може розглядатися як один із варіантів фізіологічного функціонування яєчників. Наслідки, що викликаються їх ускладненим клінічним перебігом, можуть стати причиною невідкладних оперативних втручань і грубих порушень функціонування жіночої репродуктивної системи. Особливістю функціональних кіст яєчників і тісно пов’язаних з ними таких ускладнень, як апоплексія яєчника, є їх рецидивний перебіг. Дослідження патогенетичних механізмів функціональних кіст яєчників не лише покращить результати лікування деяких форм ановуляторної безплідності, але й дозволить запропонувати патогенетично обгрунтовані заходи профілактики такої гострої хірургічної патології, як апоплексія яєчника. Зниження рецидивів функціональних кіст яєчників і їхніх ускладнень веде до зниження кількості оперованих хворих, що позитивно позначається на репродуктивній і менструальній функції жінок. Ключові слова: апоплексія яєчника, функціональні кісти, патогенетичні механізми. Резюме ОТДЕЛЬНЫЕ ПАТОГЕНЕТИЧЕСКИЕ МЕХАНИЗМЫ ФУНКЦИОНАЛЬНЫХ КИСТ ЯИЧНИКОВ И ИХ ОСЛОЖНЕНИЙ. Приведен обзор современной литературы по вопросу патогенеза функциональных кист яичников и характерного для них осложнения - апоплексии яичника. Этиопатогенез функциональных (фолликулярных, желтого тела и тека-лютеиновых) кист достаточно сложен в силу множества причин и патогенетических механизмов. Последствия, вызываемые их осложненным клиническим течением, могут стать причиной неотложных оперативных вмешательств и грубых нарушений функционирования женской репродуктивной системы. Особенностью функциональных кист яичников и тесно связанных с ними таких осложнений, как апоплексия яичника, является их рецидивирующее течение. Изучение патогенетических механизмов формирования функциональных кист яичников не только улучшит результаты лечения некоторых форм ановуляторного бесплодия, но и позволит предложить патогенетически обоснованные меры профилактики этой острой хирургической патологии. Снижение рецидивов функциональных кист яичников и их осложнений ведет к снижению количества оперированных больных, что, положительно сказывается на репродуктивной и менструальной функции женщины. Ключевые слова: апоплексия яичника, функциональные кисты, патогенетические механизмы.